Overexpression of KIF18A promotes cell proliferation, inhibits apoptosis, and independently predicts unfavorable prognosis in lung adenocarcinoma. Issue 7 (28th February 2019) - Zhong, Yonglong; Jiang, Lingyu; Lin, Hui; Li, Xiangwei; Long, Xiaomao; Zhou, Yifan; Li, Baijun; Li, Zongrong
Abstract: Kinesin family member 18A (KIF18A), as a member of the kinesin superfamily, is significantly overexpressed and abnormally functions in various human cancers. But, its expression profiling in the lung adenocarcinoma (LUAD) remains unclear. In the present work, using the data derived from the Cancer Genome Atlas (TCGA), we assessed the expression pattern and prognostic value of KIF18A in LUAD. In addition, we analyzed the underlying mechanism of its gene dysregulation. Experimental and bioinformatic analysis results showed that KIF18A expression was dramatically increased in LUAD tissues compared with the normal counterparts. Moreover, the patients with high KIF18A expression had significantly poorer overall survival (OS) and recurrence‐free survival (RFS). Univariate and multivariate analyses indicated that increased KIF18A expression was independently associated with unfavorable OS and RFS. In addition, by analyzing deep sequencing data from TCGA‐LUAD, we found that KIF18A mutation was detected in 2.6% of LUAD cases, and increased KIF18A expression was associated with genetic amplification rather than DNA methylation. Moreover, gene co‐expression network analysis revealed that a total of 339 KIF18A co‐expressed genes were detected and enriched in several tumor‐related pathways, especially cell cycle. Knockdown of KIF18A significantly inhibited cell proliferation in vitro and in vivo . Furthermore, silencing KIF18A induced LUAD cells apoptosis and arrested the cell cycle in the G2/M phase. KIF18A promotes cell proliferation, inhibits apoptosis, and is a valuable prognostic predictor and potential therapeutic target for the patients with LUAD. © 2019 IUBMB Life, 2019